The pattern of needle-stick injuries in academic hospitals in Johannesburg - Lai, Anita Pui Ching (My University, 2016)
Needle-stick injury is a common problem among health care workers (HCWs) all over the world. Globally, in 2000, there were an estimated 1000 HCW-acquired human immunodeficiency virus (HIV) infections through occupational exposure. Limited data are available in South Africa. This descriptive study documents the pattern of needle-stick injuries among registrars in the Academic Hospitals in Johannesburg, South Africa. A total of 150 registrars across different disciplines in the three Academic Hospitals in Johannesburg were interviewed, using a standardised questionnaire in 2013. The majority of the registrars interviewed (n=123, 82%) had reported a needle-stick injury. Most of the needle-stick injuries occurred during internship. Most of the doctors were working in the Departments of Surgery and Internal Medicine at the time of their injuries. The most common mechanisms of needle-stick injuries were during insertion of a drip (22%) and suturing (21%). The majority (83%) of the doctors with needle-stick injuries took post exposure prophylaxis (PEP). The combination of zidovudine and lamivudine was the most commonly used regimen. Over half (53%) of the doctors with needle-stick injuries completed the 28 days course of PEP, while the remaining doctors (47%) discontinued PEP due to side-effects and/or because they considered the treatment unnecessary. The findings in this study are similar to those reported in other studies done previously in different parts of South Africa. Adherence to PEP following needle-stick injury remains a major problem.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Medicine in Internal Medicine Johannesburg, 2016
Keywords: Needlestick Injuries; HIV; Communicable Diseases